Scaffolds based bone tissue engineering : the role of chitosan - Costa-Pinto, A. R. (2011)
As life expectancy increases, malfunction or loss of tissue caused by injury or disease leads to reduced quality of life in many patients at significant socioeconomic cost. Even though major progress has been made in the field of bone tissue engineering, present therapies, such as bone grafts, still have limitations. Current research on biodegradable polymers is emerging, combining these structures with osteogenic cells, as an alternative to autologous bone grafts. Different types of biodegradable materials have been proposed for the preparation of three-dimensional porous scaffolds for bone tissue engineering. Among them, natural polymers are one of the most attractive options, mainly due to their similarities with extracellular matrix, chemical versatility, good biological performance, and inherent cellular interactions. In this review, special attention is given to chitosan as a biomaterial for bone tissue engineering applications. An extensive literature survey was performed on the preparation of chitosan scaffolds and their in vitro biological performance as well as their potential to facilitate in vivo bone regeneration. The present review also aims to offer the reader a general overview of all components needed to engineer new bone tissue. It gives a brief background on bone biology, followed by an explanation of all components in bone tissue engineering, as well as describing different tissue engineering strategies. Moreover, also discussed are the typical models used to evaluate in vitro functionality of a tissue-engineered construct and in vivo models to assess the potential to regenerate bone tissue are discussed.